Selective lobar blockade with a Coopdech blocker combined with a double-lumen endotracheal tube for lung metastases resection by laser - Cruz,Patricia (2018)
Abstract In recent years, laser resection of lung metastases has been established as the standard procedure worldwide. To avoid airway fire, it is necessary to collapse the surgical lung. The selective lobar bronchial blockade is a technique that allows one-lung ventilation while the operated lobe is collapsed in patients with previous pulmonary resection requiring subsequent resection or with limited pulmonary reserve. We report a clinical case about our experience of a selective lobar bronchial blockade technique with a bronchial blocker (Coopdech endobronchial blocker) that was employed successfully with a double-lumen endotracheal tube in a patient with previous contralateral pulmonary resection who was scheduled for atypical resections of pulmonary metastases by laser. We selectively blocked the right intermediate bronchus for management of hypoxemia during one-lung ventilation. This technique provided adequate ventilation and oxygenation during surgery, avoiding the need of two-lung ventilation during lung metastases resection by laser. Conclusion: This case shows that if a properly positioned double-lumen tube was already in place and the patient does not tolerate one-lung ventilation because of hypoxemia, it would be possible to provide selective lobar blockade by placing a bronchial blocker through the lumen of the double-lumen tube, avoiding the use of continuous positive airway pressure during laser surgery. This technique does not disturb the operative field or interrupt the operative procedure during resection by laser, which would occur during two-lung ventilation or used of continuous positive airway pressure.